Index Development to Comprehensive Assess Liver Function during the Dairy Cows’ Transition Period in Low-Tropic Conditions. (2024)
The aimof this work was to develop a liver tissue function index during the transition period of dairy cows managed in low-tropic conditions. In two farms, twenty crossbred and synthetic native cows during the peripartumperiod were selected, and blood samples were taken on days −30 and −15 prepartum, the calving day, and 7, 20, 35, 50, 65, 80 and 105 days postpartumfor serummetabolic tests. On eachmeasurement day, body condition scores (BCS) and parameters on nitrogenmetabolism(total protein—TP, albumin—ALB, globulin—GLOB, urea), adipose tissue metabolism (cholesterol—COL, nonesterified fatty acids—NEFA) and two transaminases (alanine aminotransferase—ALT and aspartate aminotransferase—AST) were evaluated. Data analysis included the Spearman correlation, principal components, multiple linear regression and cluster analysis. Results showed that regarding the days after calving and BCS, a liver tissue function index can be constructed using the TP, urea, COL, ALT and NEFA. The estimated index generated three groupings, both by days after calving and BCS. In the former, the index discriminated the metabolic behavior in the prepartum, parturition and postpartum periods, while in the latter, the index discriminated between extreme (2.25, 2.50 and 4.25), slightly low (2.75 and 3.0) and slightly high (3.25 to 4) conditions. The results allow us to conclude that it is feasible to construct mathematical function indexes for liver function to monitor metabolic changes during highly demanding productive phases in dairy cows under tropical conditions.